Zircons underestimate mantle depletion of early Earth. (15th January 2022) - Liou, Peng; Guo, Jinghui; Mitchell, Ross N.; Spencer, Christopher J.; Li, Xianhua; Zhai, Mingguo; Evans, Noreen J.; Li, Yanguang; McDonald, Bradley J.; Jin, Mengqi
Abstract: The mechanism and timing of crustal growth and differentiation on early Earth are debated. Evidence of crustal differentiation is detectable as deviations from Earth's assumed chondritic uniform reservoir (CHUR) as crust is extracted from the mantle leading to a melt-depleted reservoir. For the long-lived zircon Lu-Hf system, no incontrovertible evidence of significant mantle depletion >3.8 Ga exists. We conduct combined U-Pb and Lu-Hf isotopic analyses for the detrital zircon from the Caozhuang supracrustal sequence in North China. The zircon Hf isotopic compositions are broadly scattered along the CHUR evolution line. However, given the possibility of potential systematic biases in zircon petrogenesis and the unique tectonic setting of early Earth, we posit that magmatism controlled by the nascent forms of plate tectonics during the Eoarchean could have likely hidden the degree of ancient crust-mantle differentiation. The non-depleted zircon Hf isotopes observed in North China and globally during early Earth may in verity imply the existence of ubiquitous depleted mantle domains at that time.